The impact of horseback riding on the balance of 7-year-old children - Ilic, P.; Aleksic-Veljkovic, A.; Hadzovic, M. (Baltic Journal of Health and Physical Activity, 2021)
Introduction: This research aimed to determine the impact of horseback riding on the balance ability of first-grade students. Material and methods: Fifty-eight students were divided into two sub-groups: twenty-eight riders and thirty non-riders. The subtest of balance is composed of nine items which were grouped into five variables: Total balance, Static balance, Dynamic balance, and Open and Closed eyes balance. The Mann-Whitney U test was used to determine the significance of the difference between the groups, and the strength of the effect of intergroup differences was determined using the Cohen criteria. Results: The results showed that there were statistically significant differences between groups in Total balance, Static, and Balance with closed eyes. Cohen's criterion indicates that there was a strong effect of intergroup differences in performance demanding balance tasks of 7-year-old children. Conclusion: It can be observed that horseback riding has the effect of reducing the difference between the maximum and minimum balance points by enhancing competencies at the minimum level.